PENINGKATAN KEMAMPUAN PEMAHAMAN KONSEPTUAL PADA OPERASI MATRIKS BERBANTUAN MATRIX CALCULATOR DI KELAS XI SMA - Hermayuda, Hermayuda; Jamiah, Yulis; Suratman, Dede (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis research aims to determine whether remedial learning which use matrix calculator can improve students’ conceptual understanding ability in matrix operation in grade XI SMAN 4 Pontianak. The research method is quantitative with pre-experimental form of research. The subject of research is grade XI SMAN 4 Pontianak. The object of the research is conceptual understanding ability of students in the operation matrix. Data obtained from the results of pretest and posttest to see students' conceptual understanding abilities. The data analysis showed that the conceptual understanding ability increased 34%. The increase is happened in each indicators conceptual understanding ability as follows: 1) the ability to mention examples and and non-examples of concepts increased 11%; 2) the ability to use, utilize and choose certain procedures or operations increased 43%; and 3) the ability to develop the terms or rules of a concept increased 39%.Keywords: Conceptual Understanding, Operation Matrix, Matrix Calculator